2009
DOI: 10.1002/hup.1048
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and anxiety: a critical review of the evidence

Abstract: The precise relationship between cannabis use and anxiety has yet to be established. Research is needed to fully clarify the mechanisms of such the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
310
3
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(345 citation statements)
references
References 101 publications
8
310
3
9
Order By: Relevance
“…The mental health of non-dependent frequent cannabis users was better than expected from studies of all (including dependent) frequent users [3,[10][11][12][13][14][15][16]20]: although mental disorders were more common in non-dependent users than in the general population (OR = 5.35, P < 0.001), this was largely attributable to (childhood) externalizing disorders (OR = 8.91, P < 0.001), whereas there was no difference in the presence of internalizing disorders. Dependent D+ frequent cannabis users with 12-month diagnosis of cannabis dependence (n = 252); D-frequent cannabis users who have never fulfilled criteria for cannabis dependence (n = 269); N2 non-users and non-frequent users in the general population (n = 1072).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The mental health of non-dependent frequent cannabis users was better than expected from studies of all (including dependent) frequent users [3,[10][11][12][13][14][15][16]20]: although mental disorders were more common in non-dependent users than in the general population (OR = 5.35, P < 0.001), this was largely attributable to (childhood) externalizing disorders (OR = 8.91, P < 0.001), whereas there was no difference in the presence of internalizing disorders. Dependent D+ frequent cannabis users with 12-month diagnosis of cannabis dependence (n = 252); D-frequent cannabis users who have never fulfilled criteria for cannabis dependence (n = 269); N2 non-users and non-frequent users in the general population (n = 1072).…”
Section: Discussionmentioning
confidence: 84%
“…However, other studies found similar rates of internalizing disorders in heavy and infrequent users [6,[17][18][19]. On one hand, these inconsistent findings may be due to small sample size, imprecise and inconsistent measurement of cannabis use or divergence in measures of mood and anxiety problems and disorders [10,11]. On the other hand, they may indicate a variation in the percentages of dependent users, suggesting that associations between internalizing disorders and heavy use without dependence are small.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Assim como para psicose 88 e ansiedade 89 , esta revisão reforça a necessidade de investigação cuidadosa de presença concomitante de uso de maconha em pacientes com transtorno bipolar e depressão, bem como a possível presença de transtornos afetivos em indivíduos diagnosticados como usuários dessa substância. Isto pode proporcionar uma abordagem mais adequada, com chances de melhor prognóstico.…”
Section: Conclusãounclassified